"An Inevitable Consequence:" Changing Ideas of Prevention in the Wake of Catastrophic Events. (October 2020) - SPEZIO, TERESA SABOL
Abstract: In the face of technology failures in preventing oil from reaching beaches and coasts after catastrophic oil spills in the 1960s and early 1970s, the oil industry and governmental officials needed to quickly reconsider their idea of prevention. Initially, prevention meant stopping spilled oil from coating beaches and coasts. Exploring the presentations at three oil-spill conferences in 1969, 1971 and 1973, this idea of prevention changed as the technological optimism of finding effective methods met the realities of oil-spill cleanup. By 1973, prevention meant stopping oil spills before they happened. This rapid policy transformation came about because the oil industry could not hide the visual evidence of the source of their technology failures. In this century, as policymakers confront invisible pollutants such as pesticides and greenhouse gases, considering ways to visually show the source of the pollution along with the effects could quicken policy decisions.